Confocal Laser Microscopy Principles and Applications in Medicine, Biology, and the Food Sciences - Lagali, Neil (IntechOpen, 2013)
Neil S. Lagali, PhD, obtained undergraduate (McMaster University) and graduate (University of Alberta) degrees in Canada. He has had several years of industry experience and held postdoctoral fellowships in Canada, The Netherlands, and Sweden. He has published over 35 peer-reviewed articles in international journals in the fields of engineering, biomedical optics, biomaterials, ophthalmology, and translational medicine. He has co-authored several book chapters, and holds patents in the fields of optical devices, biosensors, and non-invasive imaging methods. He gives numerous lectures and courses on microscopy and clinical imaging, is a regular invited speaker and session organizer at international conferences, and is an associate editor for the journal BMC Ophthalmology. Dr. Lagali is with the Department of Clinical and Experimental Medicine, Linkoping University, Sweden.